Middle-class composition and growth in middle-income countries - Razafimandimby Andrianjaka Riana (Asian Development Bank Institute (ADBI), 2017)
The impact of the expansion of the middle class in developing countries has been widely investigated in recent years. The middle class is generally apprehended by its overall demographic size, which, we believe, may hide crucial features and differences across nations because the composition of the middle class is not considered. We investigate the composition of the middle class by computing various statistical features of the distribution of income and of consumption: the incidence, the depth (the average consumption), and the heterogeneity of the middle class for a panel of 120 countries from 1985 to 2012. Furthermore, four subcategories of middle class are considered. The empirical investigation has been run on a reduced dataset of 52 middle-income countries using a two-step system GMM estimator. The bulk of bottom middle classes is found to be negatively linked to growth, whereas the composition of the middle class in those countries reveals a still large share of floating and lower middle classes. Our results also confirm that the size of a unique middle class alone is not enough to comprehend the complex mechanisms through which the expansion of the middle class impacts on growth. For middle-income countries, the consumption capacity of the middle class is what matters most and a middle class that is large and wealthier is more likely to have greater impacts.
Keywords: O11; O15; O47; 330; middle-class; income distribution; economic growth; middle-income countries